Fermentation characteristics of Pixian broad bean paste in closed system of gradient steady-state temperature field. (16th April 2022) - Ding, Wenwu; Ye, Xiaoqing; Zhao, Xiaoyan; Liu, Yan; Zhang, Manna; Luo, Yifei; Xiong, Yuanru; Liu, Yi; Che, Zhenming; Lin, Hongbin; Huang, Jiaquan; Tang, Xiaoyu
Highlights: A closed system of gradient steady-state temperature field was built to ferment PBP. The contents of physicochemical factors in the new system had been further increased. The flavor characteristics of the FG products were more stable in whole fermentation. The new system affected microbe evolutions greatly and improved the fungal diversity. Bacillus  associated with 22 flavors were identified as the core microbes in the FG. Abstract: A closed system of gradient steady-state temperature field (GSTF) was constructed to ferment Pixian broad bean paste (PBP). The contents of physicochemical factors and organic acids in the fermentation under GSTF (FG) were closer to those in the traditional fermentation (TF). The taste intensities of 8 free amino acids in the FG were higher than those in the constant temperature fermentation (CTF), but 14 in the TF showed the highest among the processes of FG, CTF and TF. The FG product had the most volatiles with 87, and its flavor properties were more stable. The FG produced great effects on the microbe evolutions especially improved the fungal diversity. Bacillus were identified as the core microbes in the FG while the roles of Staphylococcus, Lactobacillus and Pantoea were strengthened. The results indicated that the fermentation characteristics in the FG had been further improved compared with the CTF.